Prototype Sistem Monitoring Lampu Penerangan Jalan Umum Menggunakan Zigbee dan Esp32: Prototype of Public Street Light Monitoring System Using Zigbee and Esp32 - Jeki Kuswanto; Firman Asharudin; Andriyan Dwi Putra; Muhammad Tofa Nurcholis; Ashari, Wahid Miftahul (The Indonesian Journal of Computer Science, 2024)
Street lighting, or Public Street Lighting (PJU), is crucial infrastructure in an area, particularly for nighttime traffic illumination. Efficiency and monitoring pose significant challenges in PJU management. Most PJUs lack a monitoring system, making control and malfunction detection difficult. Monitoring is expected to efficiently regulate the on-off schedule and detect malfunctions. This research aims to develop a cost-effective PJU monitoring and efficiency system without replacing many existing devices. The method employs Zigbee technology and Esp32. This system is anticipated to enhance efficiency and detect issues more promptly than before.